Study Of Opportunities Of Use Of Composts Cunicoles For The Aboveground Production Of Tomato Plants In Tunisia - M’sadak, Y.; Bouallegue, A. (University of Eloued جامعة الوادي, 2015)
The present work aims to study the potential valorization of composts exhausted cunicoles for aboveground vegetable plants. In a device complete random block with three repetitions, five composts in a pure state or in mixture and a witness are tested under tomato in seedbed except ground. They got results enable us to confirm that the composts are mature. As a whole, they have availability out of high water and a content of relatively weak air, whereas the substrates containing the peat-compost mixtures have physical properties close to the standards retained in Tunisia. The vegetative behavior of these plants with respect to the variation of the composition and the average size of the particles of the substrates shows a sensitivity of the seedlings to these parameters to the beginning of their growth. Majority of the mixtures containing peat-compost gave seedlings of quality, healthy, and homogeneous. The composts prepare well with a partial use in except ground.
Articale in Journal of fundamental and Applied Sciences Vol. 07 N. 02
Keywords: Composts; porosity; thermal behavior; vegetative behavior; tomato plants.